Strategi Pengembangan Potensi Wisata Desa Bissoloro - Renold (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2019)
This research aims at identifying the strategy in developing bissoloro village. A qualitatively driven SWOT method has guided the researchers in identifying the Strength and Weakness. This research was conducted in Gowa regency in Bissoloro village from April to September 2018. The research reveals that the government, community and the villagers itself must have cooperation or agreement such Memorandum of Understanding to put the vision and mission become virtual. Tourism training and assistance seems to be problem-solving in order Bissoloro become famous tourist destinations. This research recommends the improvements of knowledge, awarness, and remembering not only limited to Regional Boards of Tourism in Gowa Regency, Community but also to the every residents of Gowa Regency and especially Bissoloro village too, so the visitors wil gain an amazing experience in Bissoloro village. An Understanding and collaboration among others in order to improve the promotion strategies especially with Tourism Institution such Tourism Polytechnic of Makassar